The Effect of Lavender Aromatherapy on Insomnia in the Elderly - Apriyanti Aini; Popy Apriyanti; Rinda Lamdayani (GLOBAL HEALTH SCIENCE GROUP, 2025)
The elderly are at risk of experiencing sleep disturbances caused by many factors. Insomnia is difficulty getting or staying asleep. Aromatherapy is a non-pharmacological treatment with essential oils obtained from plants to help improve health problems and improve sleep quality. One of the aromatherapy that can be used to overcome the problem of decreased sleep quality is lavender aromatherapy. This research was conducted to determine the effect of lavender aromatherapy on insomnia in the elderly at the Margo Mulyo Health Center, Jalan 16, Muara Sugihan District. The design of this study is to use a pre-experimental design. The sample of this study were elderly people aged 60 years and over who were obtained by purposive sampling technique with a population of 25 elderly people with insomnia. After that given lavender aromatherapy. Data analysis used the Paired T test statistic. The results showed that before giving lavender aromatherapy, the average was 17.96, which means that the respondent had insomnia behavior and after giving lavender aromatherapy, the average was 6.68, meaning that the respondent experienced a decrease in insomnia. Based on the results of bivariate analysis using the paired t-test statistic, a significance value of 0.001 was obtained with a p-value <0.05, indicating that there was an effect of giving lavender aromatherapy to insomnia in the elderly at the Margo Mulyo Health Center, Jalan 16, Muara Sugihan District.